1998
DOI: 10.1085/jgp.112.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic K+ Channel in the Heart

Abstract: The membrane-delimited activation of muscarinic K+ channels by G protein βγ subunits plays a prominent role in the inhibitory synaptic transmission in the heart. These channels are thought to be heterotetramers comprised of two homologous subunits, GIRK1 and CIR, both members of the family of inwardly rectifying K+ channels. Here, we demonstrate that muscarinic K+ channels in neonatal rat atrial myocytes exhibit four distinct gating modes. In intact myocytes, after muscarinic receptor activation, the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Membrane-associated proteins were solubilized according to a protocol previously used by us for purification of heterotrimeric G proteins (22). The membranes were incubated for 3 h in MEB buffer (20 mM HEPES, pH 8.0, 2 mM MgCl 2 , 1 mM EDTA, 100 mM NaCl, 10 mM ␤-mercaptoethanol, 1% sodium cholate, and 0.45% IGEPAL CA-630) with PI.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Membrane-associated proteins were solubilized according to a protocol previously used by us for purification of heterotrimeric G proteins (22). The membranes were incubated for 3 h in MEB buffer (20 mM HEPES, pH 8.0, 2 mM MgCl 2 , 1 mM EDTA, 100 mM NaCl, 10 mM ␤-mercaptoethanol, 1% sodium cholate, and 0.45% IGEPAL CA-630) with PI.…”
Section: Methodsmentioning
confidence: 99%
“…Single-channel Recordings and G Protein Purification-Unitary currents through K ACh channels were recorded from inside-out patches of neonatal rat atrial myocytes using a standard high resolution patchclamp method (23) as previously described (22). The composition of the bath solution was (in mM): 150 KCl, 5 EGTA, 5 glucose, 1.6 MgCl 2 , 5 HEPES (pH 7.4); the composition of the pipette solution was (in mM): 150 KCl, 1 CaCl 2 , 1.6 MgCl 2 , 5 HEPES (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…G Protein-regulated Conformational States of the GIRK Channel-Measurements of single-channel or population currents in native and chimeric GIRK channels demonstrated that heterotetrameric GIRK channels assume a number of closed and open conformations with a variable number of G␤␥ molecules bound, from a closed, non-conducting state (interpreted as G␤␥-devoid), via intermediate states with one, two, or three G␤␥ molecules bound and correspondingly increasing open probability (P o ), to a fully G␤␥-activated state with four G␤␥ bound and the highest P o (27)(28)(29)(30). Analysis of i-FRET, when combined with biochemical and functional assays, extends our understanding of the rules and modes of G protein-GIRK interactions and of the regulation of channel conformation.…”
Section: G␤␥ Is Crucial For Strong Interaction Between Girk1mentioning
confidence: 99%